Modeling and Measuring Domain-Specific Quantitative Reasoning in Higher Education Business and Economics - Susanne Schmidt; Olga Zlatkin-Troitschanskaia; Richard J. Shavelson (Frontline Learning Research, 2023)
Quantitative reasoning is considered a crucial prerequisite for acquiring domain-specific expertise in higher education. To ascertain whether students are developing quantitative reasoning, validly assessing its development over the course of their studies is required. However, when measuring quantitative reasoning in an academic study program, it is often confounded with other skills. Following a situated approach, we focus on quantitative reasoning in the domain of business and economics and define domain-specific quantitative reasoning primarily as a skill and capacity that allows for reasoned thinking regarding numbers, arithmetic operations, graph analyses, and patterns in real-world business and economics tasks, leading to problem solving. As many studies demonstrate, well-established instruments for assessing business and economics knowledge like the Test of Understanding College Economics (TUCE) and the Examen General para el Egreso de la Licenciatura (EGEL) contain items that require domain-specific quantitative reasoning skills. In this study, we follow a new approach and assume that assessing business and economics knowledge offers the opportunity to extract domain-specific quantitative reasoning as the skill for handling quantitative data in domain-specific tasks. We present an approach where quantitative reasoning – embedded in existing measurements from TUCE and EGEL tasks – will be empirically extracted. Hereby, we reveal that items tapping domain-specific quantitative reasoning constitute an empirically separable factor within a Confirmatory Factor Analysis and that this factor (domain-specific quantitative reasoning) can be validly and reliably measured using existing knowledge assessments. This novel methodological approach, which is based on obtaining information on students’ quantitative reasoning skills using existing domain-specific tests, offers a practical alternative to broad test batteries for assessing students’ learning outcomes in higher education.